2019
DOI: 10.1093/mnras/stz2492
|View full text |Cite
|
Sign up to set email alerts
|

Spectral variations of Lyman $\alpha$ emission within strongly lensed sources observed with MUSE

Abstract: We present an analysis of H I Lyman-α emission in deep VLT/MUSE observations of two highly magnified and extended galaxies at z = 3.5 and 4.03, including a newly discovered, almost complete Einstein ring. While these Lyman-α haloes are intrinsically similar to the ones typically seen in other MUSE deep fields, the benefits of gravitational lensing allows us to construct exceptionally detailed maps of Lyman-α line properties at sub-kpc scales. By combining all multiple images, we are able to observe complex str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 52 publications
7
67
2
Order By: Relevance
“…5). This resembles recent results at z ≈ 3 − 4 (Claeyssens et al 2019;Leclercq et al 2020) who report somewhat redder Lyα lines at lower surface brightness compared to the Lyα line profile at peak surface brightness, and which they suggest to be indicative of resonant scattering and to support the idea that most of the Lyα emission originates from the UV peak.…”
Section: A Single Source Illuminating a Complex Structuresupporting
confidence: 90%
“…5). This resembles recent results at z ≈ 3 − 4 (Claeyssens et al 2019;Leclercq et al 2020) who report somewhat redder Lyα lines at lower surface brightness compared to the Lyα line profile at peak surface brightness, and which they suggest to be indicative of resonant scattering and to support the idea that most of the Lyα emission originates from the UV peak.…”
Section: A Single Source Illuminating a Complex Structuresupporting
confidence: 90%
“…Simple, idealized models of Lyα radiation transfer with a central ionizing point source surrounded by a homogeneous, spherically symmetric shell of gas with a range of neutral hydrogen column density (N(H )), dust opacity, velocity, and temperature (the so-called "shell model", see e.g., Zheng & Miralda-Escudé 2002;Verhamme et al 2006) have been surprisingly successful in explaining a large variety of Lyα line profiles (e.g., Hashimoto et al 2015;Gronke 2017). Using the shell model, Verhamme et al (2018) found a correlation between FWHM and V offset (see also Claeyssens et al 2019). The left panel of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of this Lyman-α emission is complex, and only the brightest Lyman-α haloes are sufficiently extended to allow spatially resolved analyses in the absence of any lensing effect (Erb et al 2018;Leclercq et al 2020) and test predictions from simulations. MUSE observations on lensing clusters offer the power to identify extended gas around high redshift galaxies (once magnified), allowing detailed studies of the spectral line properties within multiple regions, in particular through bright Lyman-α extended haloes (Patrício et al 2016;Smit et al 2017;Caminha et al 2016b;Vanzella et al 2017;Claeyssens et al 2019). Figure 12 shows a very clear example taken from our sample of extended emission detected over the z = 4.086 source originally identified by Cohen & Kneib (2002) in RXJ1347.…”
Section: Resolved Properties Of High Redshift Galaxiesmentioning
confidence: 98%
“…Examples of pyplatefit spectral fitting, for two sources in our catalogues. Top row shows the case of the bright z = 4.03 galaxy in MACS0940(Claeyssens et al 2019) with zcon f = 3 and the bottom row a MUSELET-selected galaxy at z = 0.337 and zcon f = 2 in the same cluster field (M364). The left panel gives an overview of the spectrum, while the middle and right panels zoom in on specific spectral line fits.…”
mentioning
confidence: 99%